KELESTARIAN LINGKUNGAN SUMBER DAYA ALAM KELAUTAN DALAM IMPLIKASI REKLAMASI LAUT - Francisca, Maria; Roberto, Ignatius (Faculty of Law, University of Muhammadiyah Malang, 2017)
Reclamation is a process of making new land on land that was previously covered by water, such as river banks or coastal coasts. The new area is usually used for residential areas, industry, business, air ports, agriculture, and tourism; in fact this reclamation has a positive and negative impact on the environment and surrounding communities. The Government has provided special arrangements for the spatial plan (RTRW) of each region including the sea, but its implementation is not aligned with more attention to the economic impact than the conservation of its natural resources. The research method used is descriptive analytical and explorative, to obtain an overview of marine policy for the utilization of marine reclamation that still pay attention to the environment and its resources. The reclamation of the sea causes a disruption of the ecosystem that causes many fishermen to lose their livelihood and cause natural disasters in other locations outside the reclamation area